Human β-defensin 3 contains an oncolytic motif that binds PI(4,5)P(2) to mediate tumour cell permeabilisation - Phan, Thanh Kha (Oncotarget, 2015)
Cationic antimicrobial peptides (CAPs), including taxonomically diverse defensins, are innate defense molecules that display potent antimicrobial and immunomodulatory activities. Specific CAPs have also been shown to possess anticancer activities; however, their mechanisms of action are not well defined. Recently, the plant defensin NaD1 was shown to induce tumour cell lysis by directly binding to the plasma membrane phosphoinositide, phosphatidylinositol 4,5-bisphosphate (PI(4,5)P(2)). The NaD1–lipid interaction was structurally defined by X-ray crystallography, with the defensin forming a dimer that binds PI(4,5)P(2) via its cationic β2-β3 loops in a ‘cationic grip’ conformation. In this study, we show that human β-defensin 3 (HBD-3) contains a homologous β2-β3 loop that binds phosphoinositides. The binding of HBD-3 to PI(4,5)P(2) was shown to be critical for mediating cytolysis of tumour cells, suggesting a conserved mechanism of action for defensins across diverse species. These data not only identify an evolutionary conservation of CAP structure and function for lipid binding, but also suggest that PIP-binding CAPs could be exploited for novel multifunction therapeutics.